SrMoO4 powders processed in microwave-hydrothermal: Synthesis, characterization and optical properties - Sczancoski, J. C.; Cavalcante, L. S.; Joya, M. R.; Varela, José Arana [UNESP]; Pizani, P. S.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2008)
In this work, we report on the synthesis of SrMoO4 powders by co-precipitation method and processed in a microwave-hydrothermal at 413 K for 5 h. These powders were analyzed by X-ray diffraction (XRD), Fourier transform Raman (FT-Raman), ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL). XRD analyses revealed that the SrMoO4 powders are free of secondary phases and crystallize in a tetragonal structure. FT-Raman investigations showed the presence of Raman-active vibration modes correspondent for this molybdate. UV-vis technique was employed to determine the optical band gap of this material. SrMoO4 powders exhibit an intense PL emission at room temperature with maximum peak at 540 nm (green region) when excited by 488 nm wavelength of an argon ion laser. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: co-precipitation; microwave-hydrothermal; SrMoO4; optical band gap; photoluminescence